2024
DOI: 10.1002/advs.202306703
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Single‐Cell and Spatial Transcriptomics Reveals Heterogeneity of Early Pig Skin Development and a Subpopulation with Hair Placode Formation

Yi Wang,
Yao Jiang,
Guiyan Ni
et al.

Abstract: The dermis and epidermis, crucial structural layers of the skin, encompass appendages, hair follicles (HFs), and intricate cellular heterogeneity. However, an integrated spatiotemporal transcriptomic atlas of embryonic skin has not yet been described and would be invaluable for studying skin‐related diseases in humans. Here, single‐cell and spatial transcriptomic analyses are performed on skin samples of normal and hairless fetal pigs across four developmental periods. The cross‐species comparison of skin cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(79 reference statements)
0
0
0
Order By: Relevance
“…It has been found that the S100A9+CD29 + CD142+ biofunctional-type WJ-MSCs subpopulation exhibited best wound repair properties in vitro and in vivo , provided a reference for future development of WJ-MSC-based cell therapy for skin endogenous regeneration [ 293 ]. A recent research depicted the development of hair follicles during embryonic life and the integrated spatiotemporal transcriptomic atlas of hair follicle development in pigs through these two technologies [ 294 ]. It is worth mentioning that the data of single-cell RNA sequencing and spatial transcriptomics can be efficiently processed by artificial intelligence algorithms.…”
Section: Novel Techniques For Biomaterial-guided Wound Healingmentioning
confidence: 99%
“…It has been found that the S100A9+CD29 + CD142+ biofunctional-type WJ-MSCs subpopulation exhibited best wound repair properties in vitro and in vivo , provided a reference for future development of WJ-MSC-based cell therapy for skin endogenous regeneration [ 293 ]. A recent research depicted the development of hair follicles during embryonic life and the integrated spatiotemporal transcriptomic atlas of hair follicle development in pigs through these two technologies [ 294 ]. It is worth mentioning that the data of single-cell RNA sequencing and spatial transcriptomics can be efficiently processed by artificial intelligence algorithms.…”
Section: Novel Techniques For Biomaterial-guided Wound Healingmentioning
confidence: 99%